Fire control in tropical pine forests - Wolffsohn, A (Commenwealth Forestry Institute, University of Oxford, 1980)
At frost-free elevations in the tropics there are large natural pine forests which, with those of the southern U.S.A., form a single ecological type. Typically, the pines of these forests are undemanding of nutrients, strongly light-demanding and more resistant to fire than are their hardwood competitors. They commonly occupy latosols or red-yellow podsols whose fertility is kept at a low level through the destruction of litter by recurrent fires; these fires also favour a ground vegetation of graminoids whose perpetuation is ensured by their own inflammability. The existence of the pine forests is therefore balanced, sometimes precariously, between a condition in which fires are so frequent as to kill all tree seedlings and one in which an absence of fire permits the growth of hardwoods under whose shade the pine is unable to regenerate. Fire management planning is therefore essential in these forests and in many tropical pine plantations, but planning techniques have tended to lag behind those in the more developed countries where, over the past twenty years, there has been a major revolution in this respect. This revolution has been brought about by the search for truly objective methods of planning, stimulated and facilitated by the increasing application of computers to forest management, and culminating in the FOCUS program of the U.5. Forest Service. Although the need for objective planning is obvious, many forestry organizations, especially in the less-developed countries, lack the human and financial resources which are needed to collect and process the data used in such sophisticated programs; this paper therefore proposes certain planning techniques which may be suited to such organizations.